1993
DOI: 10.1152/jappl.1993.74.1.245
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery blood velocity and cerebral blood flow and O2 uptake during dynamic exercise

Abstract: Results obtained by the 133Xe clearance method with external detectors and by transcranial Doppler sonography (TCD) suggest that dynamic exercise causes an increase of global average cerebral blood flow (CBF). These data are contradicted by earlier data obtained during less-well-defined conditions. To investigate this controversy, we applied the Kety-Schmidt technique to measure the global average levels of CBF and cerebral metabolic rate of oxygen (CMRO2) during rest and dynamic exercise. Simultaneously with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
127
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 0 publications
8
127
1
3
Order By: Relevance
“…7 In a later study from the same group, a more robust method (SPECT scanning) for determination of global CBF was applied, and it was then found that global CBF remained constant, whereas V mean still increased. 15 This inconsistency is not readily explained, and we believe that changes in the diameter of the MCA may take place in dynamic exercise, eg, the activation of the sympathetic nervous system may constrict the larger cerebral resistance vessels concomitant to an autoregulatory dilation of the smaller resistance vessels.…”
Section: Discussionmentioning
confidence: 97%
“…7 In a later study from the same group, a more robust method (SPECT scanning) for determination of global CBF was applied, and it was then found that global CBF remained constant, whereas V mean still increased. 15 This inconsistency is not readily explained, and we believe that changes in the diameter of the MCA may take place in dynamic exercise, eg, the activation of the sympathetic nervous system may constrict the larger cerebral resistance vessels concomitant to an autoregulatory dilation of the smaller resistance vessels.…”
Section: Discussionmentioning
confidence: 97%
“…38). It has been a matter of debate whether physical activity is associated with an overall activation of the brain (30,39), but it is incontrovertible that exercise activates several regions of the brain in an intensity-dependent manner (16,44,57). Although the mechanical power output remained constant during exercise, increased difficulty in retaining power at the end of the hyperthermic cycle trial was reflected in the subjects' RPE, and it appears that brain areas associated with "central command" are activated when the "mental effort" associated with exercise is enhanced (58).…”
Section: Discussionmentioning
confidence: 99%
“…Global CBF was measured by the Kety-Schmidt technique in the desaturation mode with 133 Xe as the tracer (32,39,46). Cerebral plasma flow was calculated on the basis of the CBF and the corresponding hematocrit, and the cerebral uptake or release of a given substance was calculated as the cerebral plasma flow multiplied by the a-v difference of the substance.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24] This correlation, however, could not be substantiated by other investigations. 25 There is no data regarding these features in patients with liver diseases.…”
Section: Discussionmentioning
confidence: 99%